2007
DOI: 10.1097/ypg.0b013e32801118cd
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for an association between variants at the γ-amino-n-butyric acid type A receptor β2 locus and schizophrenia

Abstract: The alpha1/beta2/gamma2-containing heteropentamer is the most abundant gamma-amino-n-butyric acid type A receptor subtype in mammalian brains and the corresponding genes, the GABRA1, GABRB2, and GABRG2 genes, are located in chromosomal region 5q34 that several genome wide scans have implicated as a susceptibility region for schizophrenia. Given this positional and functional evidence, Lo et al. (Mol Psychiatry 2004; 9: 603-608) performed systematic linkage disequilibrium mapping of the GABAAR gene cluster on 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…GABRB2 codes for the β 2 subunit of GABA A receptor, and is part of a cluster of genes on chromosome 5q34 for the GABA A receptor, the major inhibitory neurotransmitter-gated channel receptor family in the central nervous system (CNS) [5]. Our initial findings from Han Chinese have since been validated by additional samples from the Chinese [6], Portuguese [7], German [7][9] and Japanese [9] populations, although conflicting results from Japanese [10] and German [11] populations have also been reported.…”
Section: Introductionmentioning
confidence: 88%
“…GABRB2 codes for the β 2 subunit of GABA A receptor, and is part of a cluster of genes on chromosome 5q34 for the GABA A receptor, the major inhibitory neurotransmitter-gated channel receptor family in the central nervous system (CNS) [5]. Our initial findings from Han Chinese have since been validated by additional samples from the Chinese [6], Portuguese [7], German [7][9] and Japanese [9] populations, although conflicting results from Japanese [10] and German [11] populations have also been reported.…”
Section: Introductionmentioning
confidence: 88%
“…Positive associations between GABRB2 polymorphisms and SCZ were found in Asian [ 20 22 ] and Caucasian populations [ 21 , 23 ]. However, other studies reported no association between GABRB2 and SCZ in Asian [ 24 , 25 ] or Caucasian population [ 26 ]. The results of previous two meta-analyses of GABRB2 with SCZ were inconsistent [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several candidate genes in the region have been considered including epsin 4 (CLINT1), and the GABAA locus between 160-170Mb, although the results are equivocal (Ikeda et al, 2005;Liu et al, 2005;Petryshen 2005;Pimm et al, 2005;Tang et al, 2006;Jamra et al, 2007;Lo et al, 2007). Recently, Fanous et al, (2007) presented data showing a modest association in SZ to a haplotype in the neurogenin 1 gene, which maps to ~134.9Mb.…”
Section: Introductionmentioning
confidence: 99%